Optimization of Extraction Process of Rose-orange Essential Oil and Analysis of Its Inhibitory Activity Against HCT116 Colorectal Cancer Cells - Yanjiao LIU; Yajun ZHANG; Jie CHEN; Guosheng XIAO; Qinmin ZHU; Huihui DU; Donglin YANG (Shipin gongye ke-ji)
Objective: Investigating the antitumor activity of rose-orange essential oil against colorectal cancer cells (HCT116). Methods: Ultrasound-assisted steam distillation was used to examine the effects of sodium chloride concentration, distillation time, liquid-to-material ratio, and ultrasound duration on the extraction of rose-orange essential oil. Extraction yield served as the optimization criterion, and the extraction process was optimized using a combination of single-factor experiments and response surface methodology. The in vitro anticancer activity of the essential oil was assessed using the MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] colorimetric assay. The potential mechanism underlying its inhibitory effect on colorectal cancer cell proliferation was analyzed through flow cytometry, western blotting (WB), and immunofluorescence assays. Results: The optimal extraction conditions for rose-orange essential oil were a sodium chloride concentration of 5.6%, a distillation time of 117 minutes, a liquid-to-material ratio of 12:1 mL/g, and an ultrasound duration of 33 minutes, yielding an extraction rate of 3.53%. The essential oil inhibited the growth of HCT116 cells in a dose- and time-dependent manner, with an IC50 of 933.5 μg/mL. Mechanistically, rose-orange essential oil was found to down-regulate the expression of cyclin-dependent kinase 1 (CDK1) and cyclin B1, while simultaneously inhibiting the phosphorylation of serine/threonine protein kinase Aurora A, Aurora B/C, and histone H3. These effects collectively induced G2/M phase cell cycle arrest, resulting in suppressed proliferation of HCT116 cells. This study establishes a theoretical foundation for both the extraction process and antitumor efficacy of rose-orange essential oil, thereby supporting its further development for potential therapeutic applications.